Parent's Engagement in the Learning Needs of Learners with Down Syndrome in the New Normal Education - Jeny Hinggo; Janus Naparan; Genesis Naparan (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
This study probed parental engagement in the learning needs of the learners with Down syndrome (DS) in their homes in Zamboanga Sibugay, Philippines, during this new normal education. Parents of a child with DS were the primary participants of this study. Merriam’s case study approach was utilized as a research design. Multiple data sources were considered, such as interview transcripts and observation notes during the actual interview. The results show that parents exerted more effort to ensure their children's educational success amidst the pandemic. The findings of the study reveal parents' efforts to catch the attention of their children during the delivery of learning at home. Although parents struggled to extend their children's limited attention span, they managed to find suitable strategies to keep their focus, like using different reinforcements and utilizing videos from social media platforms to teach their children. It is recommended that parents or guardians of children with DS consider pieces of training on how to effectively facilitate their children's learning process. Special Education (SPED) teachers must guide the parents on how to facilitate learning at home together with the school principal, who could initiate teaching pedagogy seminars and training for parents. The seminars and training would help parents and guardians facilitate their child's learning process.